2022
DOI: 10.3390/ma15103516
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Experimental Study on Concrete Properties of Machine-Made Tuff Sand

Abstract: Machine-made sand instead of natural sand has become an inevitable choice for the sustainable development of the concrete industry. Orthogonal experiment and grey correlation analysis were used to investigate the performance of machine-made tuff sand concrete. The optimal concrete mix ratio of machine-made sand was obtained by orthogonal test and its working performance was verified. Grey correlation analysis was applied to compare the factors affecting the mechanical properties of the machine-made sand concre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…With the increase in sand ratio, the filling effect of sand and the ball effect becomes more and more obvious, and the high fluidity of recycled concrete increases. This is relatively similar with the results of the literature [ 36 ], but the sand rate used in this paper is relatively small, so the conclusion obtained is that the flow rate increases continuously with increasing sand rate. The maximum increase value of the slump of NC-0, RC-30, RC-40, and RC-50 recycled concrete is 15 mm, 25 mm, 15 mm and 30 mm, respectively, with different sand ratios.…”
Section: Resultssupporting
confidence: 91%
“…With the increase in sand ratio, the filling effect of sand and the ball effect becomes more and more obvious, and the high fluidity of recycled concrete increases. This is relatively similar with the results of the literature [ 36 ], but the sand rate used in this paper is relatively small, so the conclusion obtained is that the flow rate increases continuously with increasing sand rate. The maximum increase value of the slump of NC-0, RC-30, RC-40, and RC-50 recycled concrete is 15 mm, 25 mm, 15 mm and 30 mm, respectively, with different sand ratios.…”
Section: Resultssupporting
confidence: 91%
“…The properties of concrete with different stone powder content and fineness modulus were tested. Gray-correlation analysis was used to calculate the correlation between the stone powder content, fineness modulus and the slump, strength of concrete [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…The lack of sand resources in China has led to the rapid development of the building materials industry, which has begun to use a large amount of machine-made sand [ 3 , 4 , 5 ]. Studies have shown that compared with natural sand, artificial sand has the advantages of abundant resources and controllable quality [ 6 ]. Machine-made sand is a kind of artificial sand made of stone crushed and screened by a sand-making machine, and the particle size is mostly less than 4.75 mm.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations